Rifabutin but not rifampicin can partly out-balance P-glycoprotein induction by concurrent P-glycoprotein inhibition through high affinity binding to the inhibitory site - Phondeth, Lottida; Kamaraj, Rajamanikkam; Nilles, Julie; Weiss, Johanna; Haefeli, Walter E; Pávek, Petr; Theile, Dirk (Archives of toxicology, 2024)
Physiology-based pharmacokinetic modeling suggests that rifabutin can out-balance P-glycoprotein (P-gp) induction by concurrent P-gp inhibition. However, clinical or experimental evidence for this Janus-faced rifabutin effect is missing. Consequently, LS180 cells were exposed to a moderately (2 µM) and strongly (10 µM) P-gp-inducing concentration of rifampicin or rifabutin for 6 days. Cellular accumulation of the fluorescent P-gp substrate rhodamine 123 was evaluated using flow cytometry, either without (induction only) or with adding rifamycin drug to the cells during the rhodamine 123 efflux phase (induction + potential inhibition). Rhodamine 123 accumulation was decreased similarly by both drugs after 6-day exposure (2 µM: 55% residual fluorescence compared to non-induced cells, P < 0.01; 10 µM: 30% residual fluorescence compared to non-induced cells, P < 0.001), indicating P-gp induction. Rhodamine 123 influx transporters mRNA expressions were not affected, excluding off-target effects. Acute re-exposure to rifabutin, however, considerably re-increased rhodamine 123 accumulation (2 µM induction: re-increase by 55%, P < 0.01; 10 µM induction: 49% re-increase, P < 0.001), suggesting P-gp inhibition. In contrast, rifampicin only had weak effects (2 µM induction: no re-increase; 10 µM induction: 16% re-increase; P < 0.05). Molecular docking analysis eventually revealed that rifabutin has a higher binding affinity to the inhibitor binding site of P-gp than rifampicin (ΔG (kcal/mol) = -11.5 vs -5.3). Together, this study demonstrates that rifabutin can at least partly mask P-gp induction by P-gp inhibition, mediated by high affinity binding to the inhibitory site of P-gp.
Keywords: Rifampin; Rifabutin; Induction; rifampin; rhodamin 123; Inhibition; P-glycoprotein; rifabutin; P-glykoprotein; Rifampicin; ATP Binding Cassette Transporter, Subfamily B, Member 1; Molecular Docking Simulation; Rhodamine 123; simulace molekulového dockingu